Reading Walter of Châtillon's Alexandreis in Medieval Anthologies - Bridges, Venetia ca. 20./21. Jh. (Mediaeval studies, 2015)
The article discusses the issue of anthologizing in English literature during the Middle Ages, as seen in Walter of Chatillon's "Alexandreis," which was first circulated in the spring of 1180. Topics discussed include the Peter Dronke's analysis on the complex and pluralist text in "Alexandreis," an overview of the structure of the Alexandreis anthology and the variety within anthologies like that of Cambridge, Corpus Christi College 406.